Simulation Of A Trash Can Using Line Follower Based On Arduino - Iqbal Hakim; Andik Prakasa Hadi (University of Science and Computer Technology, 2023)
There is a lot of dirt scattered around the State Elementary School (SDN) 03 Purwoyoso, Semarang. The habit of elementary school children and their parents is that they often throw rubbish everywhere and are lazy about throwing away the rubbish. even though there are already rubbish bins provided at the school. Children like new things, especially those shaped like toys. Garbage is a nesting place for bacteria that can cause various diseases. Humans are blessed with five senses which help them detect various things that threaten their lives. However, in the modern world, various forms of threats emerge that are not detected by our five senses, namely various types of poisons made by humans themselves. More than 75,000 synthetic chemicals have been produced by humans in the last decades. Many of them have no color, taste and smell, but have the potential to cause health hazards. Based on the problems described, the author tries to make a trash can using an Arduino-based line follower as a micro controller. This trash can can walk to the desired student line in a certain area with control carried out by a calling mechanism using a recorded voice. And if the smell is strong, the Buzzer will sound, after the students throw away the trash , the Dot Matrix LED will light up the words Thank You. It is hoped that with this rubbish bin, it will make the rubbish bin more attractive so that children will throw rubbish in its place.